Barbary partridge meat quality as affected by Hermetia illucens and Tenebrio molitor larva meals in feeds. (October 2018) - Secci, Giulia; Moniello, Giuseppe; Gasco, Laura; Bovera, Fulvia; Parisi, Giuliana
Abstract: A partial substitution (25 or 50%) of dietary protein with Tenebrio molitor (TM) and Hermetia illucens (HI) meals as protein sources in the diet of Barbary partridge ( Alectoris barbara ) has been tested in terms of raw and cooked meat quality. Twelve partridges per feeding group (control - SBM, HI25, HI50, TM25 and TM50) were slaughtered. The peeled carcasses of the HI25, HI50, TM25 and TM50 groups were heavier than those of the SBM group, both raw and cooked. The pH, color and shear force of the raw meat were not affected to any greater extent by the diet, whereas the presence of insect meal seemed to increase the yellowness index of the cooked meat. The proximate composition was unaffected by both the species and the level of insect meal, although the fatty acid profile was changed considerably. The HI and TM groups had significantly higher C18:1n-9 and lower C16:0 contents than SBM. Furthermore, Hermetia illucens, added as 50% of the dietary protein, induced a significant increase in C12:0 and C16:1n-7. As a result, the highest AI and TI were obtained for the HI50 diet (0.38 and 0.75, respectively), whereas the TM groups both had intermediate AI values (around 0.35) and the lowest TI (0.67). Finally, the cholesterol content of the birds was not affected by insect inclusion in the feeds. Abstract : Graphical abstract Highlights: Tenebrio molitor and Hermetia illucens were tested as dietary protein substitutes. Two substitution levels (25% and 50%) were compared. Barbary partridge meat quality was assessed by physical and chemical analyses. Insects meal is a promising protein source for Barbary partridge. T. molitor at 25% of substitution gives the best result in terms of meat quality.